Syntactic Functions of Tak That Used By Javanese People In Rimbo Ilir District - Asridayani Asridayani; Nova Ayu Dini Widiawati; Dodi Oktariza (Jurnal Ilmiah Langue and Parole, 2021)
The purposes of this research are to find out and to explain syntactic functions of “Tak” That Used by Javanese people in Rimbo Ilir District. This research has a several point of the functions of tak that used by Javanese people in Rimbo Ilir district. In conducting this research, the researcher uses desciptive qualitative method to do the research. While, to analyze the data, the reseacher used some theories from Randolf Quirk (1982) with the supported theory from Wedhawati (2001) and Palmer (2001). The data are found by recorded the conversation of Rimbo Ilir District. Based on the research, the researcher found three functions of Tak in Javanese language. First, the function of Tak as Personal Pronoun which generally used to the first singular person. The second, the function of Tak as Passive Markers for the first singular person which marked by affixes tak-, tak-I, tak-(a) ke, tak-ne, dan tak-ane. And the last function of tak as modal that followed by the verb after word Tak located after the word aku ‘I’.